2011
DOI: 10.1038/pr.2011.25
|View full text |Cite
|
Sign up to set email alerts
|

Birth outcomes associated with cannabis use before and during pregnancy

Abstract: Articles Clinical Investigationnature publishing group INTRODUCTION:This study aimed to examine the association between cannabis use before and during pregnancy and birth outcomes. RESULTS: Overall, 26.3% of women reported previous use of cannabis and 2.6% reported current use. Multivariate analysis, controlling for potential confounders, including tobacco smoking, alcohol consumption, and use of other illicit drugs, showed that cannabis use in pregnancy was associated with low birth weight (odds ratio (OR) = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
159
1
15

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(183 citation statements)
references
References 23 publications
8
159
1
15
Order By: Relevance
“…According to studies based on women's responses, 2-3% of women in the Avon Longitudinal Study of Parents and Children (ALSPAC) in 1991-92 reported cannabis use in the UK, 6 2.6% of women surveyed in Australia between 2000 and 2006 used cannabis, 7 3.2% used cannabis in the USA from 1997 to 2004, 8 9.5% reported cannabis use at Yale-New Haven Hospital in 1980-82, 9 and 13% reported cannabis use in the first trimester of pregnancy, and 10% reported cannabis use in the third trimester, in Ontario. A study based on either interviews or urine assays concluded that 27% of pregnant women at Boston City Hospital were cannabis users between 1984 and 1987.…”
Section: Discussionmentioning
confidence: 99%
“…According to studies based on women's responses, 2-3% of women in the Avon Longitudinal Study of Parents and Children (ALSPAC) in 1991-92 reported cannabis use in the UK, 6 2.6% of women surveyed in Australia between 2000 and 2006 used cannabis, 7 3.2% used cannabis in the USA from 1997 to 2004, 8 9.5% reported cannabis use at Yale-New Haven Hospital in 1980-82, 9 and 13% reported cannabis use in the first trimester of pregnancy, and 10% reported cannabis use in the third trimester, in Ontario. A study based on either interviews or urine assays concluded that 27% of pregnant women at Boston City Hospital were cannabis users between 1984 and 1987.…”
Section: Discussionmentioning
confidence: 99%
“…Research has consistently demonstrated that substance use during pregnancy is associated with adverse neonatal outcomes. [46][47][48] Experiencing IPV may contribute to the adoption or reinforce behavioral coping mechanisms such as tobacco and illicit substance use that may influence birth weight and gestational age at birth. 49 Future studies may want to assess socially undesirable behaviors via audio computer-assisted survey instruments to decrease underreporting.…”
Section: Severity Of Violence and Adverse Neonatal Outcomesmentioning
confidence: 99%
“…A nivel mundial, según el informe de la OMS el rango de nacimientos prematuros es de 5 al 18%. 6,[14][15] En el presente trabajo, las mujeres que sufrieron violencia, evidenciaron cifras más altas que el rango máximo a nivel mundial. La asociación entre violencia y el parto prematuro resultó fuerte e independiente de las características sociodemográficas (ser adolescente, soltera y sólo con educación primaria) y de las condiciones de salud como sífilis.…”
Section: Conclusiónunclassified